1476 Reduced Contamination of Blood Cultures Drawn in the Ed. Impact of the Implementation of an Extraction Protocol. (October 2012) - Velasco, R; Fernandez, JL; Campo, N; Puente, S; Dominguez-Gil, M; Sanchez, M; Diez, N; Gonzalez, L; Mulero, I; Centeno, F
Abstract : Introduction: Blood culture is the gold standard for the diagnosis of bacteremia. Clinical guidelines consider adequate a contamination rate of less than 3%. Between 2009 and 2010 in our service this rate was 12′56%. Therefore, in February-2011 we started a protocol for blood cultures according to the Scientific Evidence. Objectives: Analyze the impact of implementing a protocol for the extraction of hemocultures on contamination rates. Methods: Retrospective study cohort: Pre-implantation group (A): Patients whom a blood culture was taken from in our Pediatric Emergency Department between March 2009 and April 2010 and post-implantation group (B): Patients with blood culture between April 2011 and March 2012. Results: In the group A 1098 blood cultures were obtained (4'08% of 26874 patients attended) and in group B 535 (2'87% of 18628 patients, p=0.0001). A true pathogen was isolated in 11 samples in cohort A (1'00%, CI95% 0.41–1.59; 0.04% of the population attended from CI 95% 0.02 to 0.06) and in 9 of the group B (1'68%; CI 95% 0.59–2.77; 0'048% of the population attended CI 95% 0.02 to 0.08). In the group A germs considered contaminants grew in 138 blood cultures (12′56%, CI 95% 10.6–14.52) and in 34 in the B (6′35%, CI95%: 4.28–8.42). Conclusion: The development of a protocol for blood cultures extraction technique according to the Scientific Evidence is useful to reduce sample contamination, but it didn't reach to the standards of quality. Technique protocolization was associated with a significant decrease in number of blood cultures drawn.